A Novel Multiheaded Convolution Neural Network with Multilevel SVM Architecture for classification of Diabetes (International Journal of Food and Nutritional Sciences, 2022)
Classification of diabetes is an area of major concern in the field of medical science. Diabetes is not a single disease rather a group of health disorders that is hazardous to human health if not detected on time. Diabetes can be classified under three classes based on blood glucose level(BG): hyperglycemia(BG≥180mg/dL), hypoglycaemia (≤70 mg/dL) and euglycaemia (>70 and